HUBUNGAN ANTARA KEMAMPUAN PEMECAHAN MASALAH MATEMATIK DENGAN SELF EFFICACY DAN KEMANDIRIAN BELAJAR SISWA SMP - Arini Amalia; Lisdiana Futri Syafitri; Veny Triyana Andika Sari (IKIP Siliwangi, 2018)
The reasoning problem solving is aspect very important ini learning mathematics, not only increase the learning but can improve the analyze power and solve problems in learning mathematic. The student to have high self regulated learning and self efficacy to be learning better . The Purpose of this study is to determine relation reasoning problem solving mathematic with self efficacy and self regulated learning student at the eight grade of SMP Negeri 1 Kutawaluya, The 31 students. Technic used to analyze is correlation test for determine relation reasoning problem solving mathematic with self efficacy and self regulated learning students. Reaserch instrumen used was a postest reasoning problem solving and nontest questioner self efficacy and regulated learning student. The result of reaserch shows there positive correlate between reasoning problem solving mathematic and self efficacy with signification value 0,023<0,05 and self regulated learning with signification value 0,000<0,05. So, Self efficacy and self regulated learning students directly propotional to reasoning problem solving student because the higher its self efficacy and self regulated learning student then the higher reasoning problem solving students.